Modelling of wireless power transfer links based on capacitive coupling. (18th August 2016) - Dionigi, Marco; Mongiardo, Mauro; Monti, Giuseppina; Perfetti, Renzo
Summary: By using network theory, a wireless power transfer network based on coupled capacitance, that is, on electric field coupling, is numerically investigated. Three possible solutions of interest are considered: one that maximizes efficiency, one that maximizes the power delivered to the load and one that realizes power matching (conjugate matching). In each case, at a selected frequency, the optimal source/load impedances are derived in closed form. It is shown that maximum efficiency solution has the possibility of achieving almost unitary efficiency. It is also shown that, as the efficiency is increased, the power delivered to the load is decreased. Copyright © 2016 John Wiley & Sons, Ltd.